Brill's companion to Lucan - Asso, Paolo, 1965- (Brill's Companions to Classical Studies., 2011)
Although it was labeled an anti-epic for trumping the celebratory scope of the Roman national epos, Lucan's Bellum Civile is a hymn to lost republican liberty composed under Nero's tyrannical empire. Lucan lost his life in a foiled conspiracy to replace the emperor, but his poem survived the wreckage of antiquity and enjoyed uninterrupted readership. The present collection samples the most current approaches to Lucan's poem, its themes, its dialogue with other texts, its reception in medieval and early modern literature, and its relevance to audiences of all times.